Peningkatan Prestasi Belajar Matematika Menerapkan Pendekatan Contextual Teaching and Learning (CTL) di Kelas V SD - Yuli Elysa; Mai Sri Lena (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
The purpose of this study is to describe the implementation of the Contextual Teaching and Learning (CTL) approach in order to increase mathematics learning achievement on fraction division material in fifth grade SDN 04 Nanggalo. The type of research used is Classroom Action Research (PTK) by applying qualitative and quantitative approaches. The results of this study indicate an increase. The percentage acquisition in the first cycle RPP observation was 82.14% to 92.85% in the second cycle. The percentage acquisition in the implementation of learning activities in the teaching aspect of the first cycle was 83.33%, an increase of 94.44% in the second cycle. The percentage of learning activities in terms of students in the first cycle was 76.83%, an increase in the second cycle was 94.44%. Acquisition of student learning achievement in the first cycle 77.78 to 90.05 in the second cycle.